Perfil do cirurgião-dentista inserido na Estratégia de Saúde da Família em municípios do estado de Pernambuco, Brasil - Petrônio José de Lima Martelli (Ciência & Saúde Coletiva, 2010)
This article intends to approach the incorporation of the oral health to the Family Health Strategy which included the odontology professionals into the primary health care. As the odontology has the work based in a practice of healing with emphasis in restoring activities, the implantation from this new model of attention to the health is questioned in relation to the responsible for the execution of that politics - the human resources. The objective of this article is to characterize the profile of surgeons dentists inserted in the Family Health Strategy in the cities of Pernambuco state connecting it with the specificities of the program. It was used a database of the research Model of Attention in Oral Health and Education of the Surgeon DentisI inserted in the Family Health Strategy in the State of Pernambuco. The results showed that 70.4% of the surgeons dentists are female, with predominance of the age group from 31 to 49 years old, and 65.2% of those were admitted under the contract form. Concerning education, 67.8% have specialization in the Strategy of Family Health, in which 92.3% considered it pertinent, in addition 89.6% of the dentists told to accomplish educational activities.